terapia fotodinâmica no tratamento endodôntico de dentes decíduos: ensaio clínico controlado e randomizado - Okamoto, Camila Basilio (2017)
The success of the treatment is based on the decontamination of the root canal. Thus, efficacious methods have been studied as to the disinfection of the root canal systems (RCS). Of the methods studied, a highlight is the combination of conventional root canal therapy associated with laser and Antimicrobial Photodynamic Therapy (aPDT). The aim of this work was to evaluate bacterial reduction and both clinical and radiographic aspects of the root canal treatment in deciduous teeth when associated with photodynamic therapy. 32 deciduous anterior teeth diagnosed with pulp necrosis were selected. The patients were randomly divided into two groups, which underwent distinct treatments: Group I: conventional root canal treatment (n=15); Group II: conventional root canal treatment associated with aPDT (n=17). For the aPDT, Chimiolux® methylene blue (0.005%) was used as photosensitizer, applied with sterile paper cone into the root canal for 3 minutes, associated with laser application at a wavelength of 660nm (DMC, Laser THERAPY XT – EC), the canal was irradiated for 40 seconds, with the apparatus previously set at energy 4J and power 100mw. Direct contact method has been used at the entrance of the root canal. For the microbiological analysis, two samples of intracanal content were collected with paper cones. One sample was collected before and another immediately after the treatments administered in both groups. Radiographic aspects were evaluated, taking into consideration the recovery process, and we clinically observed fistula and mobility. The evaluations were carried out both 1 and 3 months after treatment. The data obtained went through statistical analysis Mann-Whitney (5%) and showed that G II had 99% bacterial reduction, whereas G I had 93%, though this difference was not statistically significant. Satisfactory tissue recovery was clinically and radiographically observed in both groups. It was therefore possible to conclude that the conventional treatment associated with aPDT was efficacious, however, it did not turn out as superior to conventional treatment alone, as far as this study is concerned.